2006
DOI: 10.1248/cpb.54.458
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antitumor Evaluation of Symmetrical 1,5-Diamidoanthraquinone Derivatives as Compared to Their Disubstituted Homologues

Abstract: In a continuation of our work on anthraquinones that widely occur in the plant kingdom and that may have biological activities, we have developed and synthesized a series of small-molecule tricyclic anthraquinone structural motifs which represents an attractive target for the rational design of new anticancer agents. [1][2][3][4][5][6][7][8] Antineoplastic drugs generally have a narrow therapeutic index and are delivered at doses close to toxicity. Despite extensive and long-standing clinical utilization, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…23,25,28,29) By comparing these results with our compounds, 20,27,30,31) it is clear that the chemical and biological activities of anthraquinones are greatly affected by various substituents of the planar ring system. 17,22,25,29,[32][33][34][35][36] Neidle et al 23,25,28,29) have also indicated that some of disubstituted anthraquinones inhibit telomerase which provide us rational design for the further investigation of SARs and comparison with their series of disubstituted homologues.…”
Section: Biological Activity and Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…23,25,28,29) By comparing these results with our compounds, 20,27,30,31) it is clear that the chemical and biological activities of anthraquinones are greatly affected by various substituents of the planar ring system. 17,22,25,29,[32][33][34][35][36] Neidle et al 23,25,28,29) have also indicated that some of disubstituted anthraquinones inhibit telomerase which provide us rational design for the further investigation of SARs and comparison with their series of disubstituted homologues.…”
Section: Biological Activity and Discussionmentioning
confidence: 61%
“…17,22,25,29,[32][33][34][35][36] Neidle et al 23,25,28,29) have also indicated that some of disubstituted anthraquinones inhibit telomerase which provide us rational design for the further investigation of SARs and comparison with their series of disubstituted homologues. Previously we described a method of synthesizing 1,5-diamidoanthraquinones (2-17) and comparing to their cytotoxicity, 31) these compounds considered as aglycon analogues of anthracycline antibiotics in which the side chains substitutes for small-molecule planar tricyclic anthraquinone structural motifs. In this investigation, we continue to focus our attention on the role of our newly synthesized 2,6-diamidoanthraquinones.…”
Section: Biological Activity and Discussionmentioning
confidence: 99%
See 2 more Smart Citations